Comparable clinical, endoscopic and histologic efficacy and tolerability of standard doses of ranitidine, omeprazole and pantoprazole in patient with gastro-esophageal reflux disease (GORD) - Pulanić, Roland; Premužić, Marina; Brkić, Tomislav Opačić, Milorad; Zorić, Vladimir, Curiš, Nada Jokić-Begić, Nataša (2003)
The aim of this double-blind, controlled and randomised study was to compare efficacy and tolerability of standard doses of ranitidine, omeprazole and pantoprazole. We concluded that pantoprazole is highly effective and well tolerated in the treatment of GORD.
Projekt MZOS
ENG